2004
DOI: 10.1016/j.rmed.2003.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and the risk of asthma in adults

Abstract: Asthma and obesity are both chronic conditions and their prevalences have risen in affluent societies. A positive association between asthma and being overweight or obese has been reported in children and women, but associations in men are less clearly described. The objective of this study was to explore the association between body mass index (BMI) and asthma in men and women of diverse ethnic and socioeconomic background living in New York State, USA. In this study, we analyzed cross-sectional data on 5524 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 33 publications
(57 reference statements)
8
87
2
3
Order By: Relevance
“…Nonetheless, the proportion of Black and Hispanic children in our study reflects the racial and ethnic profile of Central Harlem from the 2000 U.S. Census, and the high rates of current asthma and overweight observed in our dataset are similar to those in published reports of other less affluent, urban communities in New York City. 4,37,38 In short, our results are consistent with findings from other cross-sectional and prospective studies in children and adults 18,[27][28][29][30][31] and address the unresolved issue of whether gender modifies the putative association between obesity and asthma. 39 On the basis of our findings, we are in the process of implementing an intervention for overweight and at risk for overweight children with asthma enrolled in the HCZAI, which will include physical activity and nutrition sessions and an asthma educational intervention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, the proportion of Black and Hispanic children in our study reflects the racial and ethnic profile of Central Harlem from the 2000 U.S. Census, and the high rates of current asthma and overweight observed in our dataset are similar to those in published reports of other less affluent, urban communities in New York City. 4,37,38 In short, our results are consistent with findings from other cross-sectional and prospective studies in children and adults 18,[27][28][29][30][31] and address the unresolved issue of whether gender modifies the putative association between obesity and asthma. 39 On the basis of our findings, we are in the process of implementing an intervention for overweight and at risk for overweight children with asthma enrolled in the HCZAI, which will include physical activity and nutrition sessions and an asthma educational intervention.…”
Section: Discussionsupporting
confidence: 91%
“…[27][28][29] A similar pattern has been observed among children 6-14 years of age. 18 In addition, our analyses presented here utilized both a continuous measure of BMI percentile, which strengthened our statistical analysis, and the CDC-defined categories for underweight, normal weight, at risk for overweight, and overweight, which facilitated interpretation of our results.…”
Section: Discussionsupporting
confidence: 79%
“…However, much of the research in this area has focused on adults (Akerman, Calacanis, & Madsen, 2004;Ford & Mannino, 2005;Luder, Ehrlich, Lou, Melnik, & Kattan, 2004;Spivak, Hewitt, Onn, & Half, 2005). A study examing the trends in obesity among adults, used data from the NHANES I, II, and III which showed that people with asthma are far more likely to be obese than people who do not have asthma (Ford & Mannino, 2005).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…In this context, questions to ask the patient would include: In addition, more recent publications suggest that information regarding obesity, physical inactivity and time spent indoors may add to the precision of the diagnosis [5,6].…”
Section: Distinguishing Between Allergic and Non-allergic Symptomsmentioning
confidence: 99%